PENERAPAN SINGLE MOVING AVERAGE UNTUK MERAMALKAN PERMINTAAN BATU BATA PADA UD.GANTO - Sulaseh Sulaseh; Zulfi Azhar; Rohminatin Rohminatin (LPPM STMIK Royal Kisaran, 2023)
Abstract: Brick inventory is still carried out by estimating the number of bricks to be ordered without any calculations, which means that customer demand does not match the stock that has been deposited by partners. The high and low levels of customer demand will influence the number of brick sales so that UD. Ganto must be able to provide sufficient stock to match this demand. So far UD. Ganto has never implemented a forecasting system regarding the demand for bricks that must be supplied, so every time he procures bricks he will experience a shortage or even an excess. To minimize losses and errors in meeting demand for bricks in the future, UD. Ganto requires a demand forecasting system using the Single Moving Average method. The forecasting calculation process uses demand data from November 2021 to November 2022. The hypothesis in this research is forecasting demand for bricks using the Single Moving Average method at UD. Ganto can help in forecasting demand for bricks in the next period quickly and accurately so that owners can provide the right products and maximize demand management well. The way the demand forecasting system works helps the owner to achieve marketing goals and targets. Keywords: brick; forecasting; single moving average method. Abstrak: Persediaan batu bata masih dilakukan dengan cara memperkirakan jumlah batu bata yang akan dipesan tanpa adanya perhitungan sehingga membuat permintaan pelanggan tidak sesuai dengan stok yang sudah disetor oleh mitra. Tinggi rendahnya permintaan pelanggan akan mempengaruhi jumlah penjualan batu bata sehingga UD. Ganto harus mampu menyediakan stok yang cukup agar dapat mengimbangi permintaan tersebut. Sejauh ini UD. Ganto belum pernah menerapkan sistem peramalan mengenai permintaan batu bata yang harus disediakan, sehingga setiap kali melakukan pengadaan batu bata akan mengalami kekurangan atau bahkan kelebihan. Untuk meminimalisir kerugian dan kesalahan dalam memenuhi permintaan batu bata di masa yang akan datang, maka UD. Ganto memerlukan suatu sistem peramalan permintaan dengan menggunakan metode Single Moving Average. Proses perhitungan peramalan dengan menggunakan data permintaan pada bulan November 2021 sampai dengan November 2022. Adapun hipotesis dalam penelitian ini adalah peramalan permintaan batu bata menggunakan metode Single Moving Average pada UD. Ganto dapat membantu dalam meramalkan permintaan batu bata di periode berikutnya secara cepat dan akurat sehingga pemilik dapat menyediakan produk yang pas dan dapat memaksimalkan manajemen permintaan dengan baik. Cara kerja sistem peramalan permintaan membantu pemilik agar dapat mencapai tujuan serta target pemasaran. Kata Kunci: batu bata; peramalan; metode single moving average.